Influence of Board Commissioners Diversity and Audit Committee Effectiveness on the Risk of Fraud - Ni Nyoman Ari Murti; Retno Yuni Nur Susilowati (SEIKO : Journal of Management & Business, 2026)
This study examines the effect of board of commissioners' diversity and audit committee effectiveness on fraud risk in Indonesian state-owned enterprises (BUMN). Board diversity is measured by gender, age, and educational background, while audit committee effectiveness is proxied by meeting frequency and committee independence. Fraud risk is measured using the Beneish M-Score model. The study uses a sample of 19 BUMN listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with data analyzed using multiple regression analysis in SPSS 25. The results show that neither board diversity nor audit committee effectiveness has a significant effect on fraud risk. These findings suggest that fraud risk is influenced by factors beyond the governance characteristics examined in this study. Although limited to listed BUMN and selected corporate governance variables, this study provides empirical evidence that may serve as a reference for future research on the determinants of corporate fraud. Keywords: Board Of Commissioners, Effectiveness Audit Committee, Fraudulent Financial Statements.